A novel expanded metal–organic framework for balancing volumetric and gravimetric methane storage working capacities. Issue 86 (1st October 2020) - Wen, Hui-Min; Shao, Kai; Zhou, Wei; Li, Bin; Chen, Banglin
Abstract : The isoreticular extension and functionalization of NOTT-101a to UTSA-111a can improve and balance the volumetric and gravimetric methane storage working capacities simultaneously. Abstract : A novel expanded metal–organic framework (UTSA-111a) with functional pyrimidine sites exhibits simultaneously high gravimetric and volumetric methane storage working capacities of 309 cm 3 (STP) g −1 and 183 cm 3 (STP) cm −3 at 298 K and 5.8–65 bar.